Mango Cider / Siti Nur Alia Najwa Mohd Zamri ... [et al.] - Mohd Zamri, Siti Nur Alia Najwa; Abdul Azis, Nur Aina Maisarah; Mustaffa, Irdina Batrisyia; Che Ghazali, Nik Nur Fatin Elyani; Zuelkiflee, Zaharah (2025)
Mango Cider Enterprise is a local business in Malaysia and the warehouse to produce this mango cider is at Selangor. Mango Cider Enterprise sells products that can give benefits to the human body and can be consumed as soft drinks or additional ingredients in food. Our company also aims to ensure all citizens have an experience of the refreshing and benefits of the mango cider. Our vision in this project is to ensure our products can establish a name in the craft cider sector that is well known worldwide. The unique thing about our product is we use mango to make a mango cider because mango is appealing to the local palate. Next, our target customers are people who suffer from functional gastrointestinal, people who stay in Kuala Lumpur and Selangor due to the population being higher than other states, and people who have a habit of buying health-conscious foods. Our products will be promoted through social media ads, collaborations with local influencers, and put up a banner and posters. We also decided to distribute our products to pop-up stalls and retail partnerships, but we also will distribute our product by creating a website soon. Our warehouse to produce this mango cider is in Selangor.